The terpsichorean monitor. - Greene, William E. (Providence, R.I., E. A. Johnson & Co., Printers, 1889)
This manual, a compilation of previously published materials, includes a brief discussion on dancing and deportment, bows (which the author considers the "criteria of good breeding"), and a section on introductons with instructions on how to shake hands. The book also covers information on the duties of an escort, how to ask a lady to dance, and responsibilities of guests. General information is provided on quadrilles and the cotillon (also known as the German). However, the only dances described in detail are the figures for three quadrilles.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Dance; Etiquette